To patent or not to patent: dissecting moral disharmony in the context of human embryonic stem cell patenting - Atmaram Shelke; Sujata Arya; Sachchidanand Prasad; Padmakshi Sharma (Cogent Social Sciences)
The progress of science and technology, particularly in the field of human embryonic stem cells (hESCs), embodies an unparalleled perspective on improving human life. However, moral concerns regarding inventions’ patentability stemming from hESCs have long been the center of international political and moral debates. This paper aims to analyze this debate by studying the interface between science, law, and ethics in the global context. Reliance has been placed upon the legality of hESC patenting in the E.U., China, India, and the U.S.A. jurisdictions. These jurisdictions have approached this question both domestically and inconsistently. The European Patent Office has consistently denied embryonic stem cell patents due to ethical concerns regarding its Biotechnology Directive 98/44/E.C. The Court of Justice for the European Union has also judicially extended the opinion pertaining to the unethical nature of patenting hESCs. This paper dissects the elusive ‘moral acceptability’ in the context of deontological and consequentialist ethics. It advocates for legislative recognition of a system that considers ethical factors to ensure the judicious usage of the untapped potential of embryonic stem cells.